Análise da formação de filme de TEOS em diferentes concentrações na superfície do aço carbono para prevenção da corrosão - Alves, Rafaella da Silva Gomes (2019)
Carbon steel, despite its favorable mechanical properties for industrial use, is very susceptible to corrosion, requiring processes that increase its service life. One of the most commonly used ways to protect the metal is by isolating it from the corrosive medium, applying a coating on most epoxy paints, and to have greater efficiency is added with compounds that increase the adhesion on the surface of the material. Industrially chromate or phosphate based compounds are used for this purpose. However, despite presenting good performance, they generate waste with high environmental impact, both in application and disposal. An alternative to the use of these compounds is the application of zirconium and silane based film layers, which in addition to providing adhesion, are also classified as environmentally friendly. The objective of this work was to synthesize a Tetraethoxysilane-based solution (TEOS), and to evaluate the corrosion resistance of carbon steel, before and after the application of an epoxy paint layer added with the silane solution. TEOS / ethanol / water solutions were selected for this study. After having the following parameters: Concentration, pH and resting time, they presented greater stability and after being added to the substrate, with subsequent application of finishing paint, had greater protection efficiency. against corrosion. The degradation of the coatings was evaluated by electrochemical techniques such as open circuit potential (OCP) and electrochemical impedance spectroscopy (EIE). The surface characterization of the samples was performed by optical microscopy (MOP), scanning electron microscopy (SEM) with coupled dispersive energy spectroscopy (EDS) and Fourier transform infrared spectroscopy (FTIR). The concentration of Fe + 2 ions in the electrolyte was determined by infrared (IR) spectroscopy after OCP analysis on painted and treated parts. The adhesion of the paint / silane / metal system by Tensile Grip Test. Through the analyzes performed it was found that the solution of TEOS / ethanol / water in the proportion 5/53/42% at pH 4, with 48 h of rest presented greater stability and the material (carbon steel 1008) silanized with this solution. obtained better adhesion between epoxy paint and metal, as well as greater anticorrosive efficiency.